Directed cell alignment via extrusion-based 3D bioprinting for cardiac tissue engineering - Lee, Jia Min (2018)
Heart disease is the leading cause of death worldwide. Due to the limited regenerative ability of native myocardium, damaged myocardium cannot be restored. Advanced therapeutic approaches such as tissue engineering and regenerative medicine provides potential biological solutions to restore the function of damaged myocardium. Despite progresses in cardiac tissue engineering over the past decades, it is still far from mimicking the native myocardium. Some design considerations for engineering cardiac tissue includes inducing cell alignment, and attaining high cell density within a construct. Bioprinting, a computer-assisted technology, can potentially achieve the abovementioned considerations. In the native myocardium, fibre and cell orientation varies across different planar level. Bioprinting can potentially recapture this complexity through designing print path. The purpose of this project is to fabricate an engineered cardiac tissue via bioprinting. Extrusion-based bioprinting was investigated in terms of printing parameters and material properties to achieve required print resolution for efficient nutrient exchange in bioprinted cell-hydrogel construct. Next, a design framework was developed to characterize and formulate materials for bioprinting. The design framework was applied for material formulation in extrusion printing of C2C12 cells. Following which, a bioprinting strategy, termed support-assisted bioprinting, was established to produce three dimensionally defined constructs. Support-assisted bioprinting is a bioprinting strategy that uses a secondary material (support material) to provide mechanical stability for the primary material (build material) prior to crosslinking of the build material. Support-assisted bioprinting has demonstrated printing of three dimensionally defined cell-hydrogel, where hydrogel struts showed distinct 0o-90o angular difference at different height level. Cell alignment was achieved along the longitudinal axis of printed construct. The mechanism of cell-hydrogel remodelling process towards cell alignment in bioprinted construct was mapped for inducing cell alignment along strut orientation. Lastly, enabling technologies in data and cell processing were developed as translational measures towards organ printing. In data processing, machine readable print path using G-code was generated to reflect the differences in fibre orientation of left ventricle wall. This shows the feasibility of fabricating bioprinted construct that better mimics the architecture of myocardium. In cell processing towards high throughput cell aggregates formation, the use of 3D printed microfluidics was studied. These findings ascertained the potential of bioprinting towards directing cell alignment in a dimensionally defined construct.